Warfare and belligerence : perspectives in First World War studies - Purseigle, Pierre (Brill, 2005)
This collection of essays suggests some of the ways in which an interdisciplinary perspective may contribute to our understanding of the First World War. Its contributors examine the relationship between the character of the war and the nature of belligerent societies, and present original research on the comparative history of the Great War.
Keywords: World War, 1914-1918 -- Social aspects.; World War, 1914-1918 -- Historiography.; War and civilization -- History -- 20th century.; War and society -- History -- 20th century.; Guerre mondiale, 1914-1918 -- Aspect social.; Guerre mondiale, 1914-1918 -- Historiographie.; Guerre et civilisation -- Histoire -- 20e siècle.; Guerre et société -- Histoire -- 20e siècle.; HISTORY -- Military -- World War I.; Historiography; Social aspects; War and civilization; War and society; Weltkrieg -- 1914-1918; Geschichtsschreibung; Sozialgeschichte; Oxford; Eerste Wereldoorlog.; Sociale aspecten.; Geschiedschrijving.; 1900-1999; History